Spatial variation of metals and phosphorus in sediments of a river influenced by urbanization - Macedo Neto,Daniel (2017)
ABSTRACT The suspended sediments are a special compartment that characterizes the effects of land use in the watershed. Such compartment is able to trap organic compounds as well as metals in general. Spatial variation of concentrations can be accounted for the land use, soil composition and pollution. In this work, we aimed to assess the spatial variation of metals and phosphorus concentration presented in suspended sediments collected in a river under urban occupation. Using time-integrated suspended sediment samplers, samples were collectec in three sites covering different levels of occupation: Almirante Tamandaré (P1) and two in Curitiba city (Tingui Park -P2 and Barigui Park - P3). The sampler was settled to be 20 cm below the water surface and it was removed after 30 days. Twelve samples were collected to examining the following elements Al, As, Ba, Ca, Cd, Co, Cr, Cu, Fe, K, La, Mg, Mn, Na, Nb, Ni, P, Pb, Sc, Sn, Sr, Th, Ti, V, Y, Zn and Zr by ICP-OES. The first site is characterized with only 5.73% of urban area; meanwhile the site P3 has the highest urban area 54.06%. Among the twenty seven elements, nineteen showed a positive variation in concentration between collected sites, giving indication that an enrichment of metals along the river. The following elements showed positive variation: P (151.20%), La (117.98%), Cd (93.33%), Cr (71.43%), Na (68.75%), Ni (68.07%), Y (66.67%), Th (63.64%) and Zn (56.77%). Considering local reference values it is concluded that Cd, Cr, Ni, P, Y and Zn appear associated with urbanization increase in the basin; Co, Sc, Sn, Cu and Mn appear possibly associated with urbanization; Ba, La, Na, Pb and Sr show inconclusive behavior in relation with urban influence ; Al, Fe, Nb, Th, Ti, As, Ca, K, Mg, Zr and Va demonstrate not be associated with urbanization.